Digital Literacy in Visual Content: English Literature Students’ Perspective of Universitas Negeri Medan towards Instagram Posts in @rappersrelated Account - Rosenna Siahaan; Anisa Jimina Sinaga; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research explores English Literature students’ perspectives on digital literacy through visual content on the @rappersrelated Instagram account. The main focus is how this platform facilitates digital literacy skills by using design composition analysis, supporting critical thinking, and enriching aesthetic appreciation and cultural trends. This research used qualitative methods with the participation of 10 UNIMED English Literature 7th semester students to gain in-depth insights into their experiences. Thematic analysis showed that Instagram enhances visual literacy, but also faces challenges such as ambiguous interpretation and limited cultural context. The findings provide valuable insights into the role of social media in supporting digital literacy in the digital age.